2015
DOI: 10.1136/bmjopen-2014-006107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the China growth charts with the WHO growth standards in assessing malnutrition of children

Abstract: ObjectivesTo compare the difference between the China growth reference and the WHO growth standards in assessing malnutrition of children under 5 years.SettingsThe households selected from 31 provinces, autonomous regions and municipalities in mainland China (except Taiwan, Hong Kong and Macao).ParticipantsHouseholds were selected by using a stratified, multistage probability cluster sampling. Children under 5 years of age in the selected households were recruited (n=15 886).Primary and secondary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
(35 reference statements)
0
28
1
2
Order By: Relevance
“…Most studies to date have not systematically compared both undernutrition and overnutrition classification using the 3 international references examined here. Some have compared older references previously recommended by the WHO and IOTF, 33 , 34 , 35 many have assessed the WHO growth standards in children aged 0-5 years, including measures such as weight-for-height, 20 , 36 , 37 , 38 , 39 , 40 , 41 , 42 and yet others have also explored the comparability of locally constructed BMI references. 19 , 21 , 23 , 34 , 35 , 43 , 44 Much of this evidence is based on European and American populations, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 45 , 46 and research on the current references in Asian populations of wide age ranges has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have not systematically compared both undernutrition and overnutrition classification using the 3 international references examined here. Some have compared older references previously recommended by the WHO and IOTF, 33 , 34 , 35 many have assessed the WHO growth standards in children aged 0-5 years, including measures such as weight-for-height, 20 , 36 , 37 , 38 , 39 , 40 , 41 , 42 and yet others have also explored the comparability of locally constructed BMI references. 19 , 21 , 23 , 34 , 35 , 43 , 44 Much of this evidence is based on European and American populations, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 45 , 46 and research on the current references in Asian populations of wide age ranges has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this study was that the sample size was not very large; because of this, the numbers of stunting and obesity were low. The prevalence of stunting assessed using the WHO's standards and China's standards in other studies had a significant difference [31]. Whether the prevalence of stunting and obesity has a significant difference when assessed using the WHO's growth standards and China's standard should be researched with a larger sample size.…”
Section: Discussionmentioning
confidence: 88%
“…We did not find that the WHO's standards were able to reduce the detection rate of stunting and increase the detection rate of obesity significantly. Yang et al [31] also found that the prevalence of obesity assessed using the WHO's and China's standards had no significant difference. The Czech Republic compares the growth indicators of breastfed children with the national and WHO standard.…”
Section: Discussionmentioning
confidence: 98%
“…Different previous studies in different countries found that growth charts differed from the WHO growth standards with regard to the height of children. For example, the results from WHO sample children were taller than the CDC and Japanese child population, and it is expected to obtain higher prevalence stunting (< − 2 SD) of if WHO references are used; however, in the population of China, Poland, and Germany, the cutoff value for depicting stunting were higher than those reported values by WHO, resulting in the underestimate of stunting prevalence in these nations when WHO references are applied [21][22][23][24]. According to the observed difference between our study results in terms of heightfor-age and the higher centiles of our study than corresponding WHO, it is expected to have underestimates of stunting for our local population by applying WHO references.…”
Section: Discussionmentioning
confidence: 99%